Overexpression of 9-cis-Epoxycarotenoid Dioxygenase Cisgene in Grapevine Increases Drought Tolerance and Results in Pleiotropic Effects - He, Rongrong; Zhuang, Yuan; Cai, Yumeng; Agüero, Cecilia B.; Liu, Shaoli; Wu, Jiao; Deng, Shuhan; Walker, Michael A.; Lu, Jiang; Zhang, Yali (Frontiers in Plant Science, 2018)
9-cis-Epoxycarotenoid dioxygenase (NCED) is a key enzyme involved in the biosynthesis of abscisic acid (ABA), which is associated with drought tolerance in plants. An osmotic-inducible VaNCED1 gene was isolated from a drought-resistant cultivar of Vitis amurensis and constitutively overexpressed in a drought-sensitive cultivar of Vitis vinifera. Transgenic plants showed significantly improved drought tolerance, including a higher growth rate and better drought resistant under drought conditions, compared to those of wild-type (WT) plants. After water was withheld for 50 days, the upper leaves of transgenic plants remained green, whereas most leaves of WT plants turned yellow and fell. Besides the increase in ABA content, overexpression of VaNCED1 induced the production of jasmonic acid (JA) and accumulation of JA biosynthesis-related genes, including allene oxide cyclase (AOC) and 12-oxophytodienoate reductase (OPR3). Moreover, transgenic plants possessed advantageous physiological indices, including lower leaf stomatal density, lower photosynthesis rate, and lower accumulation of proline and superoxide dismutase (SOD), compared to those of WT plants, indicating increased resistance to drought stress. Quantitative real time polymerase chain reaction (RT-qPCR) analysis revealed that overexpression of VaNCED1 enhanced the expression of drought-responsive genes, such as ABA-responsive element 1(ABRE1), ABRE binding factors 2 (ABF2), plasma membrane intrinsic proteins 2 (PIP2), C-repeat/DRE-Binding Factor 4 (VvCBF4) and ABA-insensitive 5 (ABI5). Although the development of transgenic plants was delayed by 4 months than WT plants, because of seed dormancy and abnormal seedlings, the surviving transgenic plants provided a solid method for protection of woody plants from drought stress.